2019
DOI: 10.14444/6074
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-Assisted Closure: An Effective Technique to Manage Wound Complications After Metastatic Spine Tumour Surgery (MSTS)—A Case Report

Abstract: The management of wound complications following metastatic spine tumor surgery (MSTS) remains a formidable task. Plastic coverage procedures after MSTS are challenging due to unhealthy donor sites following previous radiotherapy and prolonged nonambulation. Negative pressure wound therapy (NPWT) is usually not recommended after MSTS due to fear of tumor seeding and excessive blood loss. However, in certain patients post-MSTS, who may be considered as receiving palliative treatment, NPWT can be effective in man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Knowing this can in turn help guide patient's expectations before surgery and allow the surgical team to plan ahead on the aggressiveness of debridement required. VAC is also advantageous for use in large wounds as they are able to stimulate granulation tissue in the wound bed, before secondary closure or fitting of a reconstructive graft for definitive wound closure [38 , 39] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowing this can in turn help guide patient's expectations before surgery and allow the surgical team to plan ahead on the aggressiveness of debridement required. VAC is also advantageous for use in large wounds as they are able to stimulate granulation tissue in the wound bed, before secondary closure or fitting of a reconstructive graft for definitive wound closure [38 , 39] .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the use of VAC in spinal wounds with exposed dura was also a controversial topic due to concerns of cerebrospinal fluid leak or dural tears. However, several recent studies [26 , 39 , 50] have shown the safety and efficacy of VAC even in wounds with exposed dura. Importance should be placed on a watertight dural closure before initiation of VAC therapy [50] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary skin closure was performed 14 days after negative pressure therapy. During the 3-year follow-up, no additional wound infection arose [ 34 ]. Our study emphasizes this finding that secondary skin closure following negative pressure therapy is feasible.…”
Section: Discussionmentioning
confidence: 99%
“… 3 5 This has similarly been demonstrated in radiated metastatic wounds. 4 Further, Makler et al 3 used NPWT to promote ingrowth of a dermal regeneration template in a previously irradiated and infected full-thickness calvarial wound from metastatic squamous cell carcinoma. At 6 weeks, there was significant integration of the dermal regeneration template, allowing for closure of the wound.…”
mentioning
confidence: 99%